Nilai Karakter dalam Tradisi Beseprah Adat Erau Kutai dan Implementasinya pada Pembelajaran PAI - Ulhaq Azzuhdi, Thoriq Dhia (Borneo Journal of Islamic Education, 2022)
Local wisdom culture teaches about noble character values ​​as well as education, not only teaching but shaping children's character in accordance with character values ​​in national education goals. The phenomenon of foreign cultural infiltration is increasingly unstoppable along with the rapid flow of technological development. The values ​​that are interpreted in a culture of local wisdom are starting to look vague. One of the many cultures of local wisdom is beseprah. Currently, beseprah is understood practically, namely free meals, not viewed philosophically. Besides that, between education, culture and religion there is a barrier, even though all three teach about the values ​​of goodness. This study aims to investigate the character values ​​contained in the erau Kutai traditional beseprah tradition and find out how the values ​​or meanings of beseprah are implemented in PAI subject matter for junior high and high school levels, especially in Kutai Kartanegara. This research is a qualitative research with an ethnographic approach. The data sources are: primary, consisting of interviews with the family of the Kutai Sultanate Ing Martadipura, the Kukar Education and Culture Office, Kutai cultural observers, the Kutai Literacy Movement, Arabic language lecturer at UINSI Samarinda, lecturer at the Faculty of Teacher Training for History of Unmul. And secondary from PAI books for SMP / SMA (general and madrasas) 2017/2018, 2020, Arabic dictionaries, articles and photos related to beseprah-erau. The results of the study, found that there were differences between past and present beseprah. There are values ​​contained in beseprah, namely religiosity consisting of gratitude and tolerance, nationalism consisting of discipline and preserving culture, mutual cooperation. Its implementation in PAI materials: General (Grades 7, 9, 10), Madrasah (Grades 7, 8, 9, 10, 11, 12).